A review on fabrication and pool boiling enhancement of three-dimensional complex structures. (July 2022) - Sun, Yalong; Tang, Yong; Zhang, Shiwei; Yuan, Wei; Tang, Heng
Abstract: Pool boiling with high energy conversion efficiency is critical to steam generation, electronics cooling, water purification, and other energy applications. Great efforts have been taken to the design and fabrication of high-performance pool boiling systems to meet the requirements of high heat flux applications. Three-dimensional complex structures (3D-CS) that can suppress wall superheat at the onset of nucleate boiling, enhance the heat transfer coefficient and critical heat flux are taken as an effective means to enhance the pool boiling performances. Relatively recent advances in the fabrication of 3D-CS have led to exciting enhancements in pool boiling performances and a better understanding of the underlying science. The superiority of 3D-CS in pool boiling heat transfer is mainly attributed to the larger heat transfer area, more nucleation sites, better bubble dynamics, and faster liquid rewetting rate, etc. In this review, the structural characteristics and pool boiling enhancement of 3D-CS are reviewed from the perspective of fabrication methods. Traditional machining methods, special machining methods, and other machining methods used for fabricating 3D-CS are introduced and their advantages and disadvantages are summarized. Emphasis is on the influence of fabrication methods on pool boiling enhancement of 3D-CS, which is beneficial to the application and commercialization of pool boiling systems. Moreover, some challenges and research recommendations of 3D-CS are presented for future studies. Highlights: A review on pool boiling enhancement of three-dimensional complex structures (3D-CS) is presented. The structural characteristics of 3D-CS are reviewed from the perspective of fabrication methods. Almost all the fabrication methods used to fabricate 3D-CS are summarized. The influence of fabrication methods on pool boiling enhancement of 3D-CS is discussed.